Infertilidad en el trasplante renal. - Corral Rosillo, J.; Delgado Martín, J.A.; Moreno Sierra, Jesús; Resel, Luis; Ruiz León, M.A.; Gómez Vegas, Ángel; Blázquez Izquierdo, J. (Clínicas Urológicas de la Complutense, 1999)
Sin resumen